Anti microwave radiation bamboo roofing / Norhayati Mohamad Noor ... [et al.] - Mohamad Noor, Norhayati; Mohd Kasim, Linda; Mohamat Kasim, Nazirah; Abdullah@Idris, Hasnain; Ali Mokhtar, Muhammad Fazrul Afiq; Ahmad, Azizah; Ismail, Noor Azila (2020)
Bamboo is a natural source that is abundantly available for housing roofing materials. It is a great significance to develop the roofing material with absorbing function for electromagnetic radiation shielding. This study is conducted to design a corrugated arrangement bamboo roofing microwave absorber that can absorb electromagnetic wave for frequencies 1 to 12 GHz. Three models of bamboo roofing with different corrugated arrangement namely Model A, Model B and Model C has been developed. The size of all types of proposed bamboo roofing is 60 cm width x 60 cm in length. The design is simulated using Computer Simulation Technology (CST) Microwave Studio software. The arch method is used to analyse the performance of the microwave absorber. It contains of a wooden structure in the shape of semi-circular for enabling the proper positioning towards transmitting and receiving the signals through two horn antennas. Bamboo is used as an absorbent material. Carbon from the bamboo charcoal is used to enhance the absorption performance. The expected result for bamboo roofing microwave absorber is to get a high performance of microwave absorption which is above 20 dB. From the measurement conducted all models are capable to absorb the microwave radiation. However, Model C has recorded the highest absorption level.